2022
DOI: 10.1002/jso.26816
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of the combination of primary tumor location and RAS mutational status on patients with colorectal liver metastasis undergoing hepatectomy

Abstract: Objective To assess prognostic influences of RAS mutational status and primary tumor site on cases with colorectal liver metastasis (CRLM) who underwent hepatectomy. Methods Clinicopathological data of 762 patients with CRLM who underwent hepatectomy between January 2000 and November 2018 were retrospectively analyzed. The left‐sided tumors (LST) included tumors located in the splenic flexure, descending colon, sigmoid colon, and rectum; while right‐sided tumors (RST) included those located in the cecum, ascen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…RAS mutations occur in approximately 40-50% of patients undergoing CLM resection 18 and have been associated with lower effectiveness of preoperative chemotherapy 19 and poor OS in patients with resectable CLMs. 20 Many studies have reported that patients with RAS-mutated tumours have a higher risk of intrahepatic recurrence after local treatment. 14,[21][22][23] In this study, RAS mutation was a predictor of a higher rIHR rate and worse OS after RFA for recurrent CLMs, probably because the tumour biology is more migratory and in ltrative.…”
Section: Discussionmentioning
confidence: 99%
“…RAS mutations occur in approximately 40-50% of patients undergoing CLM resection 18 and have been associated with lower effectiveness of preoperative chemotherapy 19 and poor OS in patients with resectable CLMs. 20 Many studies have reported that patients with RAS-mutated tumours have a higher risk of intrahepatic recurrence after local treatment. 14,[21][22][23] In this study, RAS mutation was a predictor of a higher rIHR rate and worse OS after RFA for recurrent CLMs, probably because the tumour biology is more migratory and in ltrative.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that RAS mutation is associated with poorer survival following curative resection of CRLM [ 14 , 29 , 30 ]. However, some studies have recently suggested that RAS mutations have different roles when predicting prognosis in CRLM with distinct clinical characteristics [ 20 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Comprehensive treatment based mainly on surgery is generally recognized as the best treatment option for patients with colorectal liver metastasis (CRLM). Several factors, including KRAS/BRAF mutation, the size of the largest tumor, the number of hepatic nodules, elevated serum tumor markers (CEA and CA 19-9), the interval between the primary tumor and the diagnosis of metastasis, the location, and the positive lymph node of the primary tumor have been found to be associated with oncological outcome after hepatectomy [ 12 , 13 , 14 , 15 , 16 ]. However, the effect of age on the long-term outcome of CRLM remains unclear.…”
Section: Introductionmentioning
confidence: 99%